2013
DOI: 10.1038/bjc.2013.15
|View full text |Cite
|
Sign up to set email alerts
|

Role of dietary polyamines in a phase III clinical trial of difluoromethylornithine (DFMO) and sulindac for prevention of sporadic colorectal adenomas

Abstract: Background:The polyamine-inhibitory regimen difluoromethylornithine (DFMO)+sulindac has marked efficacy in preventing metachronous colorectal adenomas. Polyamines are synthesised endogenously and obtained from dietary sources. Here we investigate dietary polyamine intake and outcomes in the DFMO+sulindac colorectal adenoma prevention trial.Methods:Dietary polyamine data were available for 188 of 267 patients completing the study. Total dietary polyamine content was derived by the sum of dietary putrescine, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 33 publications
(47 reference statements)
2
46
0
1
Order By: Relevance
“…Raj et al (121) have observed a significant interaction between treatment with DFMO plus sulindac and dietary polyamine intake on the risk of recurrent adenomas in a CRA prevention phase III clinical trial. Patients in the highest quartile of dietary polyamine intake have been found to have no significant metachronous adenoma risk reduction after treatment with DFMO plus sulindac, in contrast to a significant 81% risk reduction observed for patients in the lowest quartile of dietary polyamine intake.…”
Section: Influence Of Dietary Polyamines On Crc Chemopreventionmentioning
confidence: 99%
“…Raj et al (121) have observed a significant interaction between treatment with DFMO plus sulindac and dietary polyamine intake on the risk of recurrent adenomas in a CRA prevention phase III clinical trial. Patients in the highest quartile of dietary polyamine intake have been found to have no significant metachronous adenoma risk reduction after treatment with DFMO plus sulindac, in contrast to a significant 81% risk reduction observed for patients in the lowest quartile of dietary polyamine intake.…”
Section: Influence Of Dietary Polyamines On Crc Chemopreventionmentioning
confidence: 99%
“…Because the level of polyamines and the activities of polyamine biosynthetic enzymes are increased in tumor cells, ODC is one of the potential targets for the development of anticancer drugs [5,6]. Alpha-difluoromethylornithine (DFMO), which is the irreversible inhibitor of ODC, suppresses cancer development in animal models, and is being evaluated in clinical trials for the preventative treatment of colorectal cancer [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Putrescine, spermidine and spermine -key physiological polyamines -are provided endogenously from arginine and ACCEPTED MANUSCRIPT ACCEPTED MANUSCRIPT 29 ornithine, as accomplished by ornithine decarboxylase (ODC), which catalyzes the initial step in polyamine biosynthesis: conversion of ornithine to putrescine (Pegg, 2009). A series of clinical or nutritional epidemiology investigations confirm a preventive action of DFMO -an ODC inhibitor -with respect to risk of developing colorectal adenomas and CRC, thus providing support to a functional connection between polyamines and intestinal malignancy (Gerner and Meyskens, 2009;Meyskens et al, 2008;Raj et al, 2013;Vargas et al, 2012). This line of thought gains further credence from observations in experimental models: polyamine biosynthesis is commonly elevated in epithelial tumors and suppression of their endogenous production impedes tumor proliferation (Ignatenko et al, 2011;Ignatenko et al, 2009).…”
Section: Arginine: Implicated In the Diet-crc Association?mentioning
confidence: 99%
“…A combined-drug preventive therapy regimen, involving sulindac and an ODC inhibitor (DFMA), is seemingly more efficaous than either drug alone, thus suggesting an involvement of additional (Meyskens et al, 2008;Raj et al, 2013). Analogous with results from CRC-preventive therapy with NSAID, individuals at risk of developing sporadic colorectal adenomas and featuring high polyamine intake, are at less benefit from the combination therapy, relative to those of intermediate consumption (Raj et al, 2013). Lastly, patients on chronic therapy with entirely distinct drug classes, e.g.…”
Section: Potential Relevance To Red/processed Meat Consumptionmentioning
confidence: 99%